2002
DOI: 10.1097/00004714-200208000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Typical and Atypical Antipsychotics on the Prepulse Inhibition of the Startle Reflex in Patients With Schizophrenia

Abstract: Patients with schizophrenia show a loss of sensory (motor) gating, which is reflected in a reduced prepulse inhibition (PPI) of the startle reflex. Furthermore, patients with schizophrenia habituate less than healthy subjects. From previous studies, it is clear that typical antipsychotics have little or no effect on either sensorimotor gating or habituation, while only limited data is available on the effects of atypical antipsychotics on these processes.Forty-four schizophrenic patients (27 stable on typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 38 publications
6
54
1
Order By: Relevance
“…Thus, it appears that stratification of normal subjects into low and high PPI performers did not reveal the predicted enhancement of PPI by haloperidol in normal subjects with relatively low PPI levels. This negative finding is in accordance with several studies in schizophrenia patients, which showed that atypical antipsychotic medication had no PPI-enhancing effect (Grillon et al, 1992;Kumari et al, 1999;Oranje et al, 2002b;Duncan et al, 2003a, b;Perry et al, 2002;Mackeprang et al, 2002). It should be noted that the healthy subjects in our earlier study (Vollenweider et al, 2006) had lower PPI levels (mean SOA60 ¼ 8.873.3%) than did the low PPI group in the present study (mean SOA60 ¼ 43.8713.8%).…”
Section: Prepulse Inhibitionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, it appears that stratification of normal subjects into low and high PPI performers did not reveal the predicted enhancement of PPI by haloperidol in normal subjects with relatively low PPI levels. This negative finding is in accordance with several studies in schizophrenia patients, which showed that atypical antipsychotic medication had no PPI-enhancing effect (Grillon et al, 1992;Kumari et al, 1999;Oranje et al, 2002b;Duncan et al, 2003a, b;Perry et al, 2002;Mackeprang et al, 2002). It should be noted that the healthy subjects in our earlier study (Vollenweider et al, 2006) had lower PPI levels (mean SOA60 ¼ 8.873.3%) than did the low PPI group in the present study (mean SOA60 ¼ 43.8713.8%).…”
Section: Prepulse Inhibitionsupporting
confidence: 93%
“…Results of a number of cross-sectional studies suggest that patients treated for schizophrenia with atypical antipsychotics have similar PPI values as normal controls (Kumari et al, 1999(Kumari et al, , 2000Leumann et al, 2002;Oranje et al, 2002b), whereas those treated with typical antipsychotics exhibited less PPI than the control subjects (Grillon et al, 1992;Kumari et al, 1999;Oranje et al, 2002b). However, another study failed to replicate this distinction, finding that typical and atypical medications were equipotent in reversing the PPI deficit in schizophrenia patients (Quednow et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both typical and atypical antipsychotics have been tested in several clinical studies: Kumari et al (1999) reported normal PPI in schizophrenic patients treated with the atypical antipsychotic clozapine, when compared with healthy controls, whereas patients treated with typical antipsychotics showed reduced PPI. This has been replicated by Oranje et al (2002b); (for a review, see . In contrast to clozapine, Duncan et al (2003a) found that patients treated with olanzapine had levels of PPI comparable to patients treated with haloperidol or patients who are not treated at all, whereas this group as a whole showed significantly less PPI compared with healthy controls.…”
Section: Introductionmentioning
confidence: 78%
“…Several between subject, non-prospective studies of the effects of antipsychotic medications on PPI in schizophrenia revealed that patients treated with atypical medications have higher levels of PPI compared to those treated with conventional medications (Kumari et al, 1999(Kumari et al, , 2000(Kumari et al, , 2002Leumann et al, 2002;Oranje et al, 2002). However, some studies have failed to show that either atypical or conventional antipsychotic medications are lawfully associated with PPI in schizophrenia patients (Duncan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%